MENYONTEK DAN PERILAKU KORUPSI SERTA IMPLIKASI TERHADAP PENDIDIKAN - Inge Angelia; Sri Handayani; Shelvy Haria Roza (STKIP ROKANIA, 2019)
Corruption is a very urgent change in Indonesia at thistime. Corruption behavior in a person is formed by avariety of factors, one of which is fraudulent behaviorcarried out by someone at the time of education that ischeating. This article aims to discuss how to cheat asone of the factors forming corruption behavior. Theomission of cheating behavior in school is one form ofplanting corruption behavior on students. The role ofeducators here must be able to minimize cheatingbehavior so that schools do not only print graduateswho will become corruptors.